[a,b]⊆⋂n∈N(a−b−an,b+b−an)
ve
[a,b]⊇⋂n∈N(a−b−an,b+b−an)
olduğunu göstermek yeterli ve gereklidir.
(a,b∈R)(a<b)
⇒
(∀n∈N)(a−b−an<a)(b<b+b−an)
⇒
(∀n∈N)([a,b]⊆(a−b−an,b+b−an))
⇒
[a,b]⊆⋂n∈N(a−b−an,b+b−an)…(1)
−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−
x∉[a,b]
⇒
x<a∨x>b
⇒
0<a−x∨0<x−b
Arşimet Özelliği⇒
(∃n1∈N)(b−a≤n1(a−x))(∃n2∈N)(b−a≤n2(x−b))
⇒
(∃n1∈N)(x≤a−b−an1)(∃n2∈N)(x≥b+b−an2)
⇒
(n0:=max{n1,n2}∈N)(x≤a−b−an0)(x≥b+b−an0)
⇒
(n0:=max{n1,n2}∈N)(x∈(−∞,a−b−an0]∪[b+b−an0,∞))
⇒
(n0:=max{n1,n2}∈N)(x∉(a−b−an0,b+b−an0))
⇒
x∉⋂n∈N(a−b−an,b+b−an).
O halde [a,b]⊇⋂n∈N(a−b−an,b+b−an)…(2)
−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−−
(1),(2)⇒[a,b]=⋂n∈N(a−b−an,b+b−an).